Adaptación y evaluación de efectos de la intervención con video-feedback para la promocion del cuidado de calidad en la educacion inicial - Ortiz Munõz, Jenny Amanda (2016)
In daily care offered by an attachment figure to a child, it must be present, frequent and diverse interactions, and those interactions must be according with child needs (Ainsworth, 1982). The availability of the attachment figure to the child, the answers provides and if they are appropriate to child' s needs, is what is known as sensitivity (Ainsworth, 1982). This project aimed to adapt and to test the effectiveness of the video-feedback intervention to promote sensitive care and sensitive discipline (VIPP-SD), conducted with caregivers who worked in child care centers (VIPP-CC) in Uruguay. The VIPP interventions are evidence-based and using the video-feedback technique as main tool to promote sensitive care of children in their own contexts of development during early infancy. To check whether the VIPP-CC intervention was to be culturally adapted to beliefs and ideais about sensitive care of professionals in child care centers, a fust stody asked to mothers and childcare workers about their ideais of a sensitive mother in Uruguay and Brazil. Results showed highly siruilar ideal between mothers and childcare workers and across de countries. A second stody was a qualitative stody; the objective was to adapt the protocol VIPP-CC into Spanish and to test their process quality. Finally, a thiid stody was conducted to assess the impact of the VIPP-CC intervention, with an experimental methodology. Final comments were made in order to analyze the results implications for policy for early childhood.